Documentary-based climate reconstructions in the Czech Lands 1501–2020 CE and their European context - Brázdil, Rudolf; Dobrovolný, Petr; Mikšovský, Jiří; Pišoft, Petr; Trnka, Miroslav; Možný, Martin; Balek, Jan (Climate of the Past, 2022)
Annual and seasonal temperature, precipitation, and drought index (SPI – standard precipitation index, SPEI – standard precipitation evapotranspiration index, Z index, PDSI – Palmer Drought Severity Index) series covering the Czech Lands territory (now the Czech Republic) over 520 years (1501–2020 CE) reconstructed from documentary data combined with instrumental observations were analysed herein. The temperature series exhibits a statistically significant increasing trend, rising from ∼ 1890 and particularly from the 1970s; 1991–2020 represents the warmest and driest 30-year period since 1501 CE. While the long-term precipitation total fluctuations (and derived SPI fluctuations) remain relatively stable with annual and decadal variabilities, past temperature increases are the key factor affecting recent increasing dryness in the SPEI, Z index, and PDSI series. The seasonal temperature series represent a broad European area, while the seasonal precipitation series show lower spatial correlations. A statistical attribution analysis conducted utilizing regression and wavelet techniques confirmed the influence of covariates related to volcanic activity (prompting temporary temperature decreases, especially during summer) and the North Atlantic Oscillation (influential in all seasons except summer) in the Czech climate reconstructions. Furthermore, components tied to multidecadal variabilities in the northern Atlantic and northern Pacific were identified in the temperature and precipitation series and in the drought indices, revealing notable shared oscillations, particularly at periods of approximately 70–100 years.